2018
DOI: 10.1210/en.2018-00081
|View full text |Cite
|
Sign up to set email alerts
|

27-Hydroxycholesterol Is an Estrogen Receptor β–Selective Negative Allosteric Modifier of 17β-Estradiol Binding

Abstract: Estrogens bind to two nuclear estrogen receptor (ER) subtypes, ERα and ERβ, which are expressed in differing amounts in various tissues. The endogenous estrogen, 17β-estradiol (E2), binds to both subtypes with nearly equal affinity and is the prototypical agonist. Selective estrogen receptor modulators (SERMs) may bind to both subtypes with equivalent affinities but have agonist activities in some tissues while having antagonist activities in others. In the present study, we demonstrate that the first reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 63 publications
4
21
0
Order By: Relevance
“…The effect of 27HC was observed not only in H1395 cells, but also in LLC cells that are transfected with ERβ (Supplemental Figure 1 ), indicating the effect of 27HC is not H1395 cell-specific. Recently, a report indicated that 27HC acts as a negative modulator of ERβ ( 40 ). In our study, both 27HC and E 2 promoted H1395 cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of 27HC was observed not only in H1395 cells, but also in LLC cells that are transfected with ERβ (Supplemental Figure 1 ), indicating the effect of 27HC is not H1395 cell-specific. Recently, a report indicated that 27HC acts as a negative modulator of ERβ ( 40 ). In our study, both 27HC and E 2 promoted H1395 cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies identified 27HC as an endogenous selective estrogen receptor modulator (SERM) [2]. 27HC binds to both the estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) [2,3], though with greater affinity for ERβ [3]. Although the precise roles of ERβ in breast cancer remain to be delineated [4], ERβ was demonstrated to be expressed in a majority of breast cancers, including those lacking ERα expression.…”
Section: Introductionmentioning
confidence: 99%
“…This heterodimer complex can directly associate with ERα and ERβ, recruiting the co-activator p300, which then results in ligand independent activation of estrogen receptors [48]. Recently, our lab reported an alternate binding site present in ERβ, which can allosterically regulate ERβ’s activity [49]. It is possible that DIM binds and activates ER from an alternate binding site but does not allosterically influence the binding affinity of E2 in the orthosteric site in an appreciable way.…”
Section: Discussionmentioning
confidence: 99%